From manuscript to digital edition: The challenges of editing early English alchemical texts - Norja Sara (Hague, Cologne, and Antwerp, 2022)
Alchemy, later considered a pseudo-science, was one of the first experimental sciences in the Middle Ages and influenced the development of chemistry. A multitude of English medieval alchemical manuscript texts survive, written in both Latin and the vernacular. However, the uncharted material vastly outnumbers the texts edited so far, especially in the case of vernacular texts. Indeed, according to Peter J. Grund (2013: 428), the editing of alchemical manuscript texts can be called "the final frontier" in Middle English (ME) textual editing. There are currently no digital editions of ME alchemical texts, although one is under preparation (Grund 2006). Indeed, there is to my knowledge only one digital edition of alchemical texts from any period: The Chymistry of Isaac Newton, presenting Newton’s alchemical manuscript material (Newman 2005). There are also very few print editions compared to the vast amount of manuscript material: currently, only nine scholarly print editions of ME alchemical manuscript texts exist (Grund 2013: 431–32, fn. 14–15). The lack of editions may be partly due to alchemical texts having been considered too ‘obscure’ and ‘difficult’ to merit editing; alchemical language has a reputation for being vague and laden with metaphors. In general, English-language early scientific texts have not been much edited until fairly recently (cf. Pahta and Taavitsainen 2004: 3–4), and disciplines such as alchemy, considered pseudo-scientific in the present day, have been especially neglected.
However, alchemical texts present many intriguing research possibilities. In order for this branch of ME scientific writing to be used by e.g. historical linguists, more alchemical texts need to be edited – preferably in a digital form compatible with corpus search tools. This paper will discuss the challenges presented by ME alchemical texts and the ways in which a digital edition can address those challenges. A group of previously unedited and unresearched alchemical manuscript texts will act as a case study, with a focus on the issue of textual fluidity.